Investigation of Association between microRNA Variants and Risk of Rheumatoid Arthritis - Ullah, Irfan; Tariq, Muhammad Haseeb; Amir, Afreenish; Ikram, Amir; Nawaz, Mohsin (Archives of Clinical and Biomedical Research, 2023)
Introduction: Rheumatoid arthritis is a chronic autoimmune disorder that affects and damages the joints of human beings. It affects other body organs, which affects 1% of the world's population, with 6 to 60 people out of 100,000 developing the disease each year. The current study aimed to investigate the impact of variants rs11614913, rs6505162, and rs3746444 located in MIR196A2, MIR423, and MIR499, respectively, in RA patients. Methodology: These SNPs were genotyped in RA patients and age- and gender-matched healthy controls using allele-specific T-ARMS-PCR. Allelic and genotypic frequencies of each variant were noted. Furthermore, from the selected variants, the association of rs11614913 and rs6505162 variants with the risk of RA was measured using a statistical odds ratio and confidence of interval (95%). Result: In co-dominant models, the genotypic frequency of MIR423 variant rs6505162 was in cases A/A 75(35.21%), C/C 108 (50.7%) and A/C 30 (14.08%) while in controls A/A 34(16%), C/C 94(44.1%) and A/C 85(40%). These values indicate the best relationship between C/C and A/C, which were higher in cases and found significant association according to P-value and χ2. [χ2=14.03; P value=0.0009]. Conclusion: This concludes that SNPs (rs6505162) in MIR423 are the susceptibility factors for RA in the Pakistani Population. While SNPs rs11614913 in MIR196A2 have shown no association with RA.